Sustainable Printed Electrochemical Platforms for Greener Analytics - Sfragano, Patrick Severin; Laschi, Serena; Palchetti, Ilaria (Frontiers in Chemistry, 2020)
The development of miniaturized electrochemical platforms holds considerable importance for the in situ analytical monitoring of clinical, environmental, food, and forensic samples. However, it is crucial to pay attention to the sustainability of materials chosen to fabricate these devices, in order to decrease the amount and the impact of waste coming from their production and use. In the framework of a circular economy and an environmental footprint reduction, the electrochemical sensor production technology must discover the potentiality of innovative approaches based on techniques and materials that can satisfy the needs of environmental-friendly and greener analytics. The aim of this review is to describe some of the printing technologies most used for sensor production, including screen-printing, inkjet-printing and 3D-printing, and the low-impact materials that are recently proposed for these techniques, such as polylactic acid, cellulose, silk proteins, biochar.